Making Masculine Monks: Gender, Space, and the Imagined "Child" in Twelfth-Century Cistercian Identity Formation - Doss, Jacob W. (Church history, 2022)
Bernard of Clairvaux's letter to his young cousin Robert, written in the early 1120s CE, ignited a public controversy between the powerful Cluniacs and the upstart Cistercians over proper monastic practice and recruitment that smoldered throughout the twelfth century. This article examines how Cistercian polemics arose out of this new monastic competition to form Cistercian identity. Bernard of Clairvaux and the Cistercians under his influence employed a rhetoric that drew on notions of space, age, and gender to present their rivals as worldly, feminine, and immature and themselves as mature and masculine warriors on the front lines of ascetic battle against the vices. In doing so, the Cistercians deployed a gendered concept of "childhood" and "youth" that shaped their understanding of monastic conversion and progression as maturation from a worldly, feminized child to a mature and masculine monk. By centering "childhood" as a category of analysis, this article demonstrates the importance of age to Cistercian constructions of monastic masculinity. The gender-crossing martial, nuptial, and maternal imagery for which the Cistercians are famous relied on constructions of the "child." This article shows that "childhood" and "adulthood" are mutually constitutive, gendered categories and reveals that "childhood" is as important to constructing Christian masculinities as notions of "woman."